Pengaruh Kualitas Tidur terhadap Siklus Menstruasi Mahasiswi Angkatan 2023 Program Studi Sarjana Kedokteran - Tan Shi Wei; Antoni, Marcel; Rumiati, Flora; Heriyanto, Heriyanto; Rickie, Rickie (Jurnal MedScientiae, 2025)
Sleep quality plays an essential role in maintaining overall health, including the proper function of the reproductive system, which is influenced by sex hormones and circadian rhythm regulation. Medical students frequently encounter high academic demands that may disrupt their sleep patterns. Previous research has suggested a possible association between sleep quality and menstrual cycle characteristics; however, findings have been inconsistent. This study aimed to examine the relationship between sleep quality and menstrual cycle regularity among female medical students from the 2023 at the Faculty of Medicine, Universitas Kristen Krida Wacana. A descriptive-analytic design with a cross-sectional approach was applied. Data were obtained through total sampling in November 2024 using the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality and a self-reported menstrual cycle history. Of 67 respondents who met the inclusion and exclusion criteria, 51 (76.2%) reported poor sleep quality, while 16 (23.8%) had good sleep quality. Furthermore, 40 participants (59.7%) had normal menstrual cycles, and 27 (40.3%) reported irregular cycles. Statistical analysis revealed no significant association between sleep quality and menstrual cycle regularity (p = 0.794) among these students.